Early predictors of disability in paediatric multiple sclerosis: evidence from a multi-national registry. Issue 12 (30th September 2022) - Sharmin, Sifat; Malpas, Charles B; Roos, Izanne; Diouf, Ibrahima; Alroughani, Raed; Ozakbas, Serkan; Izquierdo, Guillermo; Eichau, Sara; Horakova, Dana; Havrdova, Eva K; Patti, Francesco; Terzi, Murat; et al.
Abstract : Background: Early recognition of markers of faster disability worsening in paediatric-onset multiple sclerosis (MS) is a key requisite of personalised therapy for children with MS at the earliest possible time. Objective: To identify early predictors of rapid disability accrual in patients with paediatric-onset MS. Methods: Using the global MSBase registry, we identified patients who were <18 years old at the onset of MS symptoms. The clinico-demographic characteristics examined as predictors of future MS Severity Score (MSSS) included sex, age at symptom onset, absence of disability at the initial assessment, maximum Expanded Disability Status Scale (EDSS) score, relapse frequency and presence of brainstem, pyramidal, visual or cerebellar symptoms in the first year. A Bayesian log-normal generalised linear mixed model adjusted for cumulative proportion of time on higher-efficacy disease-modifying therapies (DMTs) was used to analyse the data. Results: 672 patients (70% female) contributing 9357 visits were included. The median age at symptom onset was 16 (quartiles 15–17) years. Older age at symptom onset (exp(β)=1.10 (95% CI 1.04 to 1.17)), higher EDSS score (1.22 (1.12 to 1.34)) and pyramidal (1.31 (1.11 to 1.55)), visual (1.25 (1.10 to 1.44)) or cerebellar (1.18 (1.01 to 1.38)) symptoms in the first year were associated with higher MSSS. MSSS was reduced by 4% for every 24% increase in the proportion of time on higher-efficacy DMTs (0.96 (0.93 to 0.99)). Conclusions: A relatively later onset of MS in childhood, higher disability and pyramidal, visual or cerebellar symptoms during the first year predicted significant worsening in disability in patients with paediatric-onset MS. Persistent treatment with higher-efficacy DMTs was associated with a reduced rate of disability worsening.